Our experience with surgical management of myasthenia gravis - Pesula, E; Grosmanová, Taťána (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1989)
The authors' own experience obtained from surgical management of the myasthenia gravis in the First Department of Surgery, Teaching Hospital, Palacký University in Olomouc, within 1963 to 1985 are analyzed. The total of 50 operations on the thymus were performed in this period. Five myasthenics were operated on. Four of them had the thymoma associated with MG, one had no thymoma either prior to or during the surgery. Once the MG was associated with a benign thymoma, three times with a malignant thymoma. All the thymomas could be radically extirpated. The late results of the treatment are given. Some more recent examination methods are evaluated. The conclusion sums up the results of surgical MG management, indication to operation and its tactics stressing the necessity of complex multidisciplinary care of MG patients.
Keywords: thymom; Female; Adult; dospělí; Thymectomy; Humans; ženské pohlaví; Thymoma; mužské pohlaví; Male; lidé; myasthenia gravis; lidé středního věku; Middle Aged; nádory brzlíku; Myasthenia Gravis; Thymus Neoplasms; thymektomie